Amenable epigenetic traits of dental pulp stem cells underlie high capability of xeno-free episomal reprogramming - Chandrabose, S.T.; Sriram, S.; Subramanian, S.; Cheng, S.S.; Ong, W.K.; Rozen, S.; Abu Kasim, N.H.; Sugii, S. (BioMed Central, 2018)
Background: While a shift towards non-viral and animal component-free methods of generating induced pluripotent stem (iPS) cells is preferred for safer clinical applications, there is still a shortage of reliable cell sources and protocols for efficient reprogramming. Methods: Here, we show a robust episomal and xeno-free reprogramming strategy for human iPS generation from dental pulp stem cells (DPSCs) which renders good efficiency (0.19%) over a short time frame (13-18 days). Results: The robustness of DPSCs as starting cells for iPS induction is found due to their exceptional inherent stemness properties, developmental origin from neural crest cells, specification for tissue commitment, and differentiation capability. To investigate the epigenetic basis for the high reprogramming efficiency of DPSCs, we performed genome-wide DNA methylation analysis and found that the epigenetic signature of DPSCs associated with pluripotent, developmental, and ecto-mesenchymal genes is relatively close to that of iPS and embryonic stem (ES) cells. Among these genes, it is found that overexpression of PAX9 and knockdown of HERV-FRD improved the efficiencies of iPS generation. Conclusion: In conclusion, our study provides underlying epigenetic mechanisms that establish a robust platform for efficient generation of iPS cells from DPSCs, facilitating industrial and clinical use of iPS technology for therapeutic needs.